Lingga Yoni Jejak Peradaban Masyarakat (Jawa, Bali) dari Perspektif Positivistik - Sunoto, Sunoto (citeus, 2017)
Lingga-Yoni artifact is found to be a part of various traces of Javanese civilization. The artifact was created and is still meaningful for Javanese society. Its meaning depends on the point of view taken. As a part of critical thought, there are several points of view selected to find the meaning of the lingga-yoni artifact, they are anthropological, formal-structural, mythological, philosophical, and positivistic. From the positivistic point of view, lingga-yoni artifact might be assessed as the basis of probability and causal laws viewed from the relevant construct of positivistic thoughts.